Optimal production planning of concentrated apple and pear juice plants - Catala, Luis Pedro (2013)
This paper presents a mathematical model aimed at optimizing the yearly profit of a concentrated apple and pear juice plant through the appropriate design of its production plan. This study assumes a business scenario where the products are devoted to the international market and therefore the production schedule is dictated by a fluctuating prices scenario due to the worldwide supply/demand tradeoff. Moreover, raw fruit is available only during the relatively short harvest season and suffers juice yield reduction during storage. In this context, decisions related to the manufacturing of each juice variety to exploit favorable prices, while minimizing juice yield loss due to fruit aging are not intuitive. Scenario studies, together with sensitivity analysis on some model parameters are developed to illustrate the performance of the proposed approach.